Foundations of Software Science and Computation Structures 16th International Conference, FOSSACS 2013, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2013, Rome, Italy, March 16-24, 2013, Proceedings - Pfenning, Frank (Theoretical Computer Science and General Issues, 2013)
This book constitutes the proceedings of the 16th International Conference on Foundations of Software Science and Computational Structures, FOSSACS 2013, held as part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2013, which took place in Rome, Italy, in March 2013 The 28 papers presented in this volume were carefully reviewed and selected from 109 submissions. They are organized in topical sections named: models of computation; reasoning about processes; bisimulation; modal and higher-order logics; reasoning about programs; computational complexity; quantitative models; and categorical models.